An ultrastructural study of the surface and attachment structures of Paradiplozoon homoion (Bychowsky & Nagibina, 1959) (Monogenea: Diplozoidae) - Konstanzová, Veronika; Koubková, Božena; Kašný, Martin; Ilgová, Jana; Dzika, Ewa; Gelnar, Milan (Parasites & vectors, 2017)
BACKGROUND: Species of Diplozoon Palombi, 1949 (Monogenea: Diplozoidae) are blood-feeding ectoparasites mainly parasitising the gills of cyprinid fishes. Although these parasites have been the subject of numerous taxonomic, phylogenetic and ecological studies, the ultrastructure of the surface and haptor attachment structures remains almost unknown. In this study, we used transmission electron microscopy to examine the ultrastructure of attachment clamps and neodermal surface of Paradiplozoon homoion (Bychowsky & Nagibina, 1959), family Diplozoidae Palombi, 1949, thereby broadening our knowledge of platyhelminth biology. RESULTS: The hindbody surface of P. homoion is distinctly ridged, each ridge being supported by several muscle fibers and equipped with scales on the surface plasma membrane. Such structures have not been recorded previously in species of the family Diplozoidae. Comparisons of the surface structure of different body parts revealed slight differences in the thickness and number of organelles. Each of the clamps has a flattened bowl-like structure composed of sclerites, movable skeletal-like structures that are anchored by robust, radially oriented muscle bundles. The base of the posterior median plate sclerites is equipped with glandular cells possessing secretory vesicles. CONCLUSION: This study brings detailed ultrastructural data for the surface and haptoral attachment clamps of P. homoion and provides new insights into the ultrastructure of Diplozoidae. Glandular cells at the base of the attachment clamps responsible for sclerite development in diplozoid species were observed for the first time. Our findings support the hypothesis that the structure of particular neodermal compartments is similar within the Platyhelminthes. On the other hand, the diplozoid glandular system and the mechanism of sclerite development clearly merits further attention.
Keywords: Fish Diseases; Trematode Infections; Gills; Animals; žábry; Tegument; nemoci ryb; transmisní elektronová mikroskopie; infekce červy třídy Trematoda; Cyprinidae; Microscopy, Electron, Transmission; Ultrastructure; zvířata; Attachment clamps; fylogeneze; Neodermis; Trematoda; Paradiplozoon homoion; Phylogeny